A Non-Probabilistic Time-Storage Trade-off for Unsalted Hashes - Schardong, Frederico; Formolo, Daniel (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2016)
This work proposes a new cryptanalytic non-probabilistic trade-off for unsalted hashes. It presents the main cryptanalytic trade-offs, making a comparison with the proposed method. Although the number of hash operations to recover an element is high compared with the traditional methods, the new method has the advantage of guaranteed success on the recovery of hashes, minimal and sequential disk read operations, unlike the existing probabilistic trade-offs.